Eco-print Hijab through STEAM Project-Based Learning in Research Class - Wulandari, Susanti; Mahmudah, Eneng (Universitas Sebelas Maret, 2024)
Environmental education is increasingly being given attention in school curricula in response to global environmental challenges. This article explores the implementation of science learning at the high school level with the STEAM-project-based learning method for the production of Eco-print Hijab. The research method used is a case study, and data are collected through interviews, observations, and analysis. This approach creates an innovative and creative learning environment. The data was analyzed qualitatively with a descriptive approach. The results of the study show that the process of making Eco-print Hijab is influenced by various factors, including the variety of fabric, the type of plant/leaf chosen, the source of the dye, the time of steaming, the strength of the squeeze, and other factors. Eco-print Hijab is a unique creative product with high artistic value. The STEAM-project-based learning method is considered effective in creating creative products. The practical implications of this study are innovative learning models in schools